Closing Clostridium botulinum Group I Genomes Using a Combination of Short- and Long-Reads - Gonzalez-Escalona, Narjol; Sharma, Shashi K. (Frontiers in Microbiology, 2020)
Clostridium botulinum is a gram positive, spore-forming anaerobic bacterium that produces botulinum neurotoxin (BoNT). Closing their genomes provides information about their neurotoxin cluster arrangement(s) and location (e.g. chromosome or plasmid) which cannot be assessed using draft genomes. Therefore, we tested the use of long-read sequencing (Nanopore sequencing) in combination with short-read sequencing to close two toxin-producing strains. These genomes could be used by the Public Health Emergency Preparedness and Response staff during botulism outbreaks. The genomes of two toxin-producing Clostridium botulinum strains, one from an environmental sample (83F_CFSAN034202) and the other from a clinical sample (CDC51232_CFSAN034200), were sequenced using MinION and MiSeq devices. The genomes, including the chromosomes and the plasmids, were closed by a combination of long-read and short-read sequencing. They belonged to different C. botulinum sequence types (ST), with 83F belonging to ST4 and CDC51232 to ST7. A whole genome SNP analysis clustered these two strains with strains in Lineage 2 (e.g. 6CDC297) and 4 (e.g. NCTC2916) from Group I, respectively. These two strains were also bivalent strains with the BoNTB and BoNTA4 clusters located in the larger plasmid for CDC51232, and the BoNTB and BoNTA1 clusters located both in the chromosome for 83F. Overall, this study showed the advantage of combining these two sequencing methods to obtain high quality closed C. botulinum genomes that could be used for SNP phylogenies (source tracking) as well as for fast identification of BoNT clusters and their gene arrangements.